Analysing the effectiveness of digital illustration in motion graphics for Malaysian sparkling drink products / Nur Khadijah Zaifa Kamaruzaman ... [et al.] - Zaifa Kamaruzaman, Nur Khadijah; Che Din, Sharkawi; Mohd Lazim, Nur Aniza; Mohamed Ghazali, Nabila Aimi (Universiti Teknologi MARA, Perak, 2023)
The integration of graphics and illustration art into the commercial design process has emerged as a significant factor influencing the level of commercial design. Digital illustration has proven a practical strategic tool in marketing and advertising, particularly in the sparkling drink industry. The method used in this research is a qualitative method in which content analysis was utilised to analyse the digital illustration styles in motion graphics for Malaysia's sparkling drinks. According to the research, applying various illustration styles in the Malaysian sparkling drink industry effectively conveys brand messages. The result reveals that companies in the industry may employ several illustration styles to communicate their brand's unique identity and values effectively. Additionally, the study pointed out the beneficial effects of incorporating digital illustrations in motion graphics, including more brand identification, improved customer engagement and enhanced advertising effectiveness.